Factors Associated with Delays in Early Stroke Detection among Older Adults - Yusniawati, Yustina Ni Putu; Putra, I Gde Agus Shuarsedana; Lewar, Emanuel Ileatan; Dari, Ni Putu Desy Ratna Wulan; Juniawan, Putu Denny; Meikayani, Ida Ayu Putu Carisa; Irawan, I Kadek Feri; Djami, Rani Velentina Angelina (JURNAL INFO KESEHATAN, 2026)
Stroke is a medical emergency caused by disrupted blood circulation to the brain, leading to rapid neurological dysfunction and potentially fatal outcomes if not treated promptly. Optimal management must be initiated within the first three hours after symptom onset, known as the golden period. However, many stroke patients experience delays in receiving treatment, particularly in the prehospital phase, where more than 80% of cases fail to obtain timely medical intervention due to late recognition of stroke signs and symptoms (Satapathy, et al., 2025). Several factors related to early stroke detection require further investigation to determine the most dominant contributors to delayed detection and management. This study aimed to analyze the factors associated with the occurrence of delays stroke detection among older adults in five Banjar in Melinggih Village. A descriptive correlational analytic design with a cross-sectional, conducted over three months from July to September 2025, with 292 respondents were selected proportionally based on inclusion and exclusion criteria. Data were collected from older adult using structured questionnaires from AST (Face, Arm, Speech, Time), the Los Angeles Prehospital Stroke Screen (LAPSS), and PACS (Medic Prehospital Assessment for Code Stroke). Data analysis was performed using spearman rho and multivariable logistic regression. The results demonstrated significant associations between early stroke detection and knowledge (p<0.001; OR=5.702), attitude (p<0.001; OR=4.820), awareness (p<0.001; OR=4.820), assistant support (p<0.001; OR=4.620), information access ((p<0,001; OR=0.474), education background (p<0,001; OR=4.820). Multivariate analysis identified knowledge factor associated early stroke detection occurrence (P<0.001; OR =5.502; 95% CI: 1.938–9.843). In conclusion, delays in early stroke detection among older adults is significantly associated with knowledge, attitudes, awareness, family accompaniment, access to information, and educational background. Enhancing knowledge among older adults, along with strengthening public health programs that provide stroke related education and reinforce the role of elderly health cadres in monitoring older adults’ health, is essential to reduce delays in early stroke detection among this population.